2016
DOI: 10.1021/acscatal.6b01717
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of a Carbon-Supported Single-Site Molybdenum Dioxo Catalyst for Biodiesel Synthesis

Abstract: A single-site molybdenum dioxo catalyst, (O c ) 2 Mo­(O) 2 @C, was prepared via direct grafting of MoO2Cl2(dme) (dme = 1,2-dimethoxyethane) on high-surface-area activated carbon. The physicochemical and chemical properties of this catalyst were fully characterized by N2 physisorption, ICP-AES/OES, PXRD, STEM, XPS, XAS, temperature-programmed reduction with H2 (TPR-H2), and temperature-programmed NH3 desorption (TPD-NH3). The single-site nature of the Mo species is corroborated by XPS and TPR-H2 data, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 103 publications
(146 reference statements)
7
53
0
Order By: Relevance
“…The Mo 3d5/2 peak is found to be 232.6 eV with a spin orbit splitting of 3.1 eV. These results are in good agreement with previously reported XPS data [26] and support our hypothesis of the existence of a Mo(VI) dioxo species.…”
Section: Catalyst Recyclabilitysupporting
confidence: 92%
See 3 more Smart Citations
“…The Mo 3d5/2 peak is found to be 232.6 eV with a spin orbit splitting of 3.1 eV. These results are in good agreement with previously reported XPS data [26] and support our hypothesis of the existence of a Mo(VI) dioxo species.…”
Section: Catalyst Recyclabilitysupporting
confidence: 92%
“…All chemicals were used as received and without further purification unless otherwise noted. Mo@C was prepared and fully characterized previously by this laboratory from (dme)Mo(=O) 2 Cl 2 (dme=1,2‐dimethoxyethane) and activated carbon …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…10-12 ,. 4,5,6 Further, the ν CO values IR spectra similarly provideinge essential details of the local environments of metal sites on solid surfaces. 713 The typical mononuclear metal carbonyl complex on a metal oxide support is heterogeneous, characterized by a smear of species and broad ν CO bands, but Miessner et al 8 14 showed that mononuclear rhodium carbonyls bonded to dealuminated HY zeolite are characterized by narrow ν CO bands, indicating that the zeolite bonding sites are almost all the same.…”
mentioning
confidence: 99%